PERAN ORANG TUA DALAM MEMBENTUK KEPRIBADIAN ANAK DI RUMAH PADA MURID SDN 06 PAL 100 BERMANI ULU RAYA KAB. REJANG LEBONG - MARTINAH, WITRI; ZULAIHA, SITI (Universitas Islam Negeri Raden Intan Lampung, 2018)
The role of parents in the formation of a mature personality in children is necessary, because parents are educators and the foundation of the child's personality, the basic personality will be useful or contribute to future experience in the future in this case the authors find the existence of the forms of personality, confident, unfriendly, easily giving up, being rude and being rude, disrespectful and crybaby-the personality form is very influential to the personality because the child is familiar with the personality this is a bad thing and will affect the next life and can harm yourself and others, both within the school environment and the social environment of the community. The purpose of this study is to know how the child's personality in Class IV, how the role of parents in shaping the child's personality at home, the impact of the role of parents on the child's personality in school.The type of this research is qualitative descriptive field research data collection is done by interviewing observation and documentation. Data analysis technique used is Miles and Huberman model analysis with steps: reduction, display data, and clocusing drawing / verification. Test the credibility of the data used is tringgulasi techniques and sources.The results of research are: 1) Personality of children of Class IV SDN 06 Pal 100 with lack of parent role at home hence personality less good like not confident, not polite, not tough and easy to give up, not polite, not self study. 2) The role of parents in shaping the personality of the father's son acts as an educator, seeker and provider of livelihoods, source and giver of protective affection and a sense of security in the family. Mother acts as an educator, a source and a giver of compassion. 3) The results of the role of parents at home to the child's personality in school in terms of learning if children get the role of parents then the child will appear more ready in learning because it is motivated at home, but otherwise if the functions and roles of parents are not done well then children will be seen in their daily lives such as when the child is back from school children become lazy in learning and when in school children are often noisy in the classroom and how the child mingle with peers also more lead to mischief.